The Effect of Debt to Equity Ratio Analysis, Return on Equity, and Earning Per Share on the Stock Prices of Companies Incorporated in the Jakarta Islamic Index (JII) - Izzati Rizal (International Journal of Education, Information Technology, and Others, 2022)
The stock price is the main reason for investors to buy shares as a form of investment in the company. Therefore, investors need information about the factors that affect stock prices either directly or indirectly. The information needed is the company's financial statements. This study examines the effect of Debt to Equity Ratio, Return On Equity, and Earning Per Share on Stock Prices incorporated in the Jakarta Islamic Index (JII) in 2018-2020. The data used is the company's financial statements for 3 consecutive years incorporated in the Jakarta Islamic Index. The analysis method used is multiple linear regression, t-test, and F test with a significance level of 5%, classical assumption test